Tratamento seletivo na secagem de vacas leiteiras - Lopes, Luis Oliveira (2018)
The aim of this study was to evaluate the use of antibiotics in cows during the dry period. The survey was performed on 148 teats during the dry period, with samples collection in the period D-70 (70 days before delivery) and D14 (14 days after delivery). The milk samples were collected for the Strip Cup Test (SCT), California Mastitis Test (CMT), Microbiological Culture, Somatic Cell Count (SCC), Somatic Cell Score (SCS) and Hyperkeratosis (HK). The groups in which there were not microorganisms grow were divided into two groups, the first group only the internal sealant in the teat was used (Group 1) and another group with the intramammary antibiotic use associated with the internal sealant (Group 2). Teats which were considered positive, with microbiological growth, were treated with the intramammary antibiotic associated with the internal sealant (Group 3). In the comparison of the results of the CMT test between D-70 and D14, a statistical difference was observed in Groups 2 and 3. Group 3, which comprises the positive teats in D-70 presented a reduction of 83.87% and 32.26% in the CMT test between D-70 and D14. Regarding HK, group 1 and 2 had a statistical difference in relation to group 3 in D-70 and D14. As for the numbers of bacteria isolated in D-70 and D14, there was no difference comparing Group 1 and Group 2, unlike Group 3, which had difference. Group 1 and Group 2 were all negative teats in D-70, showing that the intramammary antibiotic did not influence the outcome of D14. In group 3 there was a reduction of isolates from 62 to 15 in D14. The most prevalent microorganism was Streptococcus agalactiae with 43.37% of the total isolates, followed by Staphylococcus aureus (16.87%) and Corynebacterium spp. (13.25%) and Coagulase negative Staphylococcus (SCN) (10.84%). The selective treatment of teats in dry dairy cows has advantages over Blanket Dry Cow Therapy by reducing the indiscriminate use of antibiotics, avoiding bacterial resistance, ensuring better milk quality and a greater food safety. Antibiotics should only be used for teats with subclinical mastitis, with microbiological culture at the end of lactation performed by fourth individual mammary.